2006
DOI: 10.1103/physreve.74.045102
|View full text |Cite
|
Sign up to set email alerts
|

Transition in the pattern of cracks resulting from memory effects in paste

Abstract: Experiments involving vibrating pastes before drying were performed for the purposes of controlling the crack patterns that appear in the drying process. These experiments revealed a transition in the direction of lamellar cracks from perpendicular to parallel when compared with the direction of the initial external vibration as the solid volume fraction of the paste is decreased. This result suggests a transition in the memory in paste, which is visually represented as morphological changes in the crack patte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
81
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 17 publications
0
81
1
1
Order By: Relevance
“…Earlier studies have elucidated the mechanism of desiccation crack formation for various grain-liquid mixtures [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The mixtures typically consist of a skeleton of solid grains and pore spaces that are filled with either liquid or air bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have elucidated the mechanism of desiccation crack formation for various grain-liquid mixtures [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The mixtures typically consist of a skeleton of solid grains and pore spaces that are filled with either liquid or air bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Since such pastes remember the directions of flow, we can imprint (in principle) any flow patterns into paste to make various crack patterns, such as lamellar, radial, ring, spiral, and so on. 13,14) Thus, we know that there are two types of memory effects, and we need to investigate what is essential to their emergence. It is reported that densely packed inelastic particles exhibit jamming phenomena, which can be an origin of irreversible and persistent deformation, i.e., plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Recently, it has been reported that paste remembers the direction of external fields and the morphology of desiccation cracks can be controlled by memory effects of paste. [12][13][14] If we mix powder with water, pour the mixture into a container to make a thin layer, and dry it at a room temperature, desiccation cracks emerge with characteristic sizes of these fragments proportional to the depth of the mixture. [15][16][17][18] When the mixture contains a lot of water, it can be regarded as a viscous Newtonian fluid, and we usually get isotropic and cellular desiccation crack patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the nanolithography and/or the combination of the two multi-scale lithography techniques show weaknesses in throughput and cost caused by the direct-writing-based nanofabrication processes and scale-up or scale-down lithography processes in series 2,3 . Cracks are considered material failures and have never been welcome in micro/ nanofabrication processes, but active manipulation of cracking phenomena made it possible to produce various micro and nanoscale patterns, showing remarkable potential for a novel unconventional patterning technique [4][5][6][7][8][9][10][11][12][13][14] . However, the crackingbased micro and nanopatterns show several weaknesses and limitations: only one-dimensional (1D) or limited 2D patterns because of the direction of applied stresses [4][5][6][7][8][9] and the crystallinity of a substrate 11 , respectively; the insufficient controllability of the geometric dimension (for example, width, depth and length) of cracks/patterns caused by the incapability of manipulating the stress strength [6][7][8][10][11][12][13][14] ; low success rates in patterning because of unwanted crack formation 4,9,11 ; low throughput in fabrication because of sequential and multiple fabrication processes 11,14 ; incompatibility with other microfabrication processes [5][6][7]10 and low reproducibility by micromoulding and/or soft lithography [10]…”
mentioning
confidence: 99%